Fluorescence activation, patterning and enhancement with photogenerated radicals, a prefluorescent probe and silver nanostructures. Issue 9 (28th January 2021) - Golian, Karol P.; Akari, Aviya S.; Hodgson, Gregory K.; Impellizzeri, Stefania
Abstract : We designed a switchable fluorophore activated by UVA light and a radical initiator, for optical lithography with concomitant metal-enhanced fluorescence by silver nanoparticles. Abstract : We synthesized a dual fluorogenic system based on a boron-dipyrromethene (BODIPY) dye coupled with a paramagnetic 2, 2, 6, 6-tetramethylpiperidine- N -oxyl (TEMPO) nitroxide. Electron exchange facilitates the non-radiative relaxation of the singlet state of the chromophore, partially quenching the fluorescence from the BODIPY moiety. Nonetheless, the system can be 'activated' in solution or thin polymer films by ultraviolet (UVA) light in the presence of a free radical initiator. UVA illumination promotes the decomposition of the initiator, resulting in the release of a carbon-centered free radical. The dye-TEMPO probe can concomitantly trap the radical or undergo H-abstraction. Both processes consequently turn on the fluorescence and are reversible in nature. We used this protocol to optically imprint a fluorescent pattern on a surface. Moreover, we investigated metal-enhanced fluorescence (MEF) effects by silver nanostructures (AgNP) as a means to improve the performance of our molecular strategy for fluorescence activation. Overall, this work contributes toward the development of improved nanoparticle–dye systems for applications of light-activated fluorescence such as multicolour fluorescence patterning and microscopy, where shorter reaction times, milder conditions, reversibility and a more diverse selection of both excitation sources and emission wavelengths are beneficial.